Analisis Hubungan Curah Hujan dan Kecepatan Angin Terhadap Pencemaran Sampah Plastik Permukaan Laut di Teluk Manta, Nusa Penida, Bali - Adilvina, Akwila; Hendrawan, I Gede; Suteja, Yulianto; Yuda, I Wayan Andi (Bumi Lestari; Vol 25 No 2 (2025)DO - 10.24843/blje.2025.v25.i02.p02, 2025)
High rainfall can increase the flow of waste from land to sea through rivers and floods, while wind speed affects the movement and distribution of waste in the sea and coast. Through the 2022 analysis, it was found that in the northwest season, particles dominated from the northwest of Nusa Penida with a particle contribution from Bali of 1.15 tons. This study hypothesizes that the entry of waste into the waters of Manta Bay is influenced by rainfall and wind speed from waste sources. Multiple linear regression analysis was carried out to see the relationship between rainfall and wind speed at the waste source and the concentration of waste in Manta Bay, Nusa Penida, Bali. This study uses a quantitative method (Apuke, 2017) with the data collection stage covering data on the number and type of plastic waste from visual survey transects, rainfall and wind. From the research conducted, it was found that the concentration of waste ranged from 0 - 0.24 pieces / m^2. Soft waste dominates with a percentage of 74%. Waste in the waters of Manta Bay is dominant during the west season, which is estimated to occur due to the movement of wind from the Pacific to the Indian Ocean which causes an increase in sea water volume. During the west season, the wind and current slow down, with the topography of the coast in the form of a bay so that it becomes a sink or trap for plastic waste. The results of the multiple linear regression test were obtained with a significant value of 0.008 <0.05 so that it was accepted and the Rsquare value or coefficient was 0.959, meaning that rainfall and wind speed together/simultaneously had a significant positive effect on the concentration of plastic waste found in Manta Bay, Nusa Penida, Bali.